2017
DOI: 10.5664/jcsm.6702
|View full text |Cite
|
Sign up to set email alerts
|

Veterans Affairs Primary Care Provider Perceptions of Insomnia Treatment

Abstract: Study Objectives: Insomnia is a widespread issue among United States adults and rates of insomnia among veterans are even higher than the general population. Prior research examining primary care provider (PCP) perspectives on insomnia treatment found that: sleep hygiene and pharmacotherapy are the primary treatments offered; PCPs tend to focus on perceived causes of insomnia rather than the insomnia itself; and neither patients nor providers are satisfied with insomnia treatment options. Although insomnia com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 39 publications
5
40
0
Order By: Relevance
“…24 In a survey with VA primary care providers who worked in medical centers with access to CBT-I, only 29% reported utilizing CBT-I to treat insomnia. 25 In contrast, over 70% of these providers depended on medications and sleep hygiene.…”
Section: Clinician Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…24 In a survey with VA primary care providers who worked in medical centers with access to CBT-I, only 29% reported utilizing CBT-I to treat insomnia. 25 In contrast, over 70% of these providers depended on medications and sleep hygiene.…”
Section: Clinician Barriersmentioning
confidence: 99%
“…A common theme in studies with clinicians is that they lack familiarity with CBT-I treatment components and are unsure of the effectiveness. 4,6,[25][26][27][28][29][30] In a survey study with Belgian family physicians, only 35% indicated that their knowledge of nonpharmacologic approaches to insomnia was sufficient. 30 This finding was replicated in a VA survey study in which 82% of primary care providers had some familiarity with CBT-I, but only 10% had a good understanding and use it in their practice.…”
Section: Clinician Barriersmentioning
confidence: 99%
“…11 It is with this information in mind that the paper by Ulmer and colleagues in this issue of Journal of Clinical Sleep Medicine explores the beliefs, attitudes, and behaviors of VA primary care clinicians regarding insomnia. 12 Overall, the results of this study show that insomnia is frequently misreported or not reported in the medical record, on many occasions mishandled through provision of suboptimal care, and often just plain missed-not discussed or brought up at all. Ulmer and colleagues report that the plurality of clinicians surveyed believed that insomnia symptoms were experienced by 20% to 39% of their patients.…”
mentioning
confidence: 89%
“…What is also disturbing is that Ulmer and colleagues report that even within the VA system, recommended first-line treatments are not used. 12 When clinicians were asked how they responded to insomnia, the most common response was counseling on healthy sleep hygiene, which is known to be ineffective for treating insomnia.…”
mentioning
confidence: 99%
“…depression, hypertension, work absenteeism). Not surprisingly, insomnia complaints often remain undiagnosed and untreated (Cheung et al ., ; Ulmer et al ., ). When treatment is initiated, treatment trajectories vary widely depending on individual and contextual factors, such as knowledge about treatment options, availability of treatment and the type of professional from whom someone seeks help (physician, psychologist, pharmacist, nurse).…”
mentioning
confidence: 97%